High-performance management practices and employee outcomes in Denmark - Annalisa Cristini; Tor Eriksson; Dario Pozzoli (Institute for the Study of Labor (IZA), 2012)
High-performance work practices are frequently considered to have positive effects on corporate performance, but what do they do for employees? After assessing the correlation between organizational innovation and firm performance, this article investigates whether high-involvement work practices affect workers in terms of wages, wage inequality and workforce composition. The analysis is based on a survey directed at Danish firms matched with linked employer-employee data and also examines whether the relationship between high-involvement work practices and employee outcomes is affected by the industrial relations context.
Keywords: C33; J41; J53; L20; 330; workplace practices; wage inequality; workforce composition; hierarchy; Arbeitsorganisation; Arbeitsproduktivität; Lohnstruktur; Arbeitsbeziehungen; Privatwirtschaft; Dänemark